Analysis Of Linguistic Intelligence In Students' Audiovisual-Based Story Content Understanding Of Class VIII - Siregar, Junifer; Saragih, Vita Riahni; Tampubolon, Novita Sari (Jurnal Ilmu Sosial Mamangan, 2024)
Understanding reading aims to obtain information from sources of knowledge conveyed through writing. Understanding is the most important component in reading activities with the aim of obtaining clear information from what is read. Understanding a story can be done by reading books or listening to stories either orally or through media. To obtain good understanding, it is necessary to train linguistic intelligence, because understanding the contents of the story is related to linguistic intelligence. Good linguistic intelligence is defined as the ability to recognize, know, understand the meaning of a word, and express it orally or in writing. From the results of observations of the linguistic intelligence of class VIII students of SMP Negeri 2 Pematangsiantar, they differ from each other. This means that there are various understandings of children in understanding the contents of fictional stories, such as students who can already accept and there are also students who cannot accept learning. Understanding the contents of the story, apart from being influenced by word mastery, can also be influenced by the media used by the teacher. Therefore, the use of interesting media can increase students' interest in listening, reading, speaking, and writing a story even with a long plot. To be able to determine a person's linguistic intelligence, one can find out the mastery of words that can be known from four aspects, namely: listening, reading, writing and speaking. Linguistic intelligence in understanding the contents of fictional stories if taught with the right and interesting media will also increase. Therefore, to improve linguistic intelligence, researchers choose audio-visual media.